Odpowiedzi

2010-03-04T18:44:49+01:00
A)6(x-4)-2=6x-24-2=6x-26

b)2(x+1)-3(x-1)=2x+2-3x+3=-x+5

c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14

d)5(x-y-1)-4)y+2)=5x-5y-5-4y-8=5x-9y-13

e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b

f)½(4x-4)-2x= 2x-2-2x=2
2 3 2
2010-03-04T18:45:22+01:00
6(x-4)-2=6x-24-2=6x-26
2(x+1)-3(x-1)=2x+2-3x+3=-x+5
-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
5(x-y-1)-4(y+2)=5x-5y-5-4y-8=5x-9y-13
2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
½(4x-4)-2x=2x-2-2x=-2
2010-03-04T18:47:05+01:00
A)6(x-4)-2=6x-24-2=6x-26
b)2(x+1)-3(x-1)=2x+1-3x+3=-x+4
c)-3(y-2)+4(y+2)=-3y+6+4y+8=y=14
d)5(x-y-1)-4(y+2)=5x-5y-5-4y-8=5x-9y-5
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f)½(4x-4)-2x=2x-2-2x=-2
1 4 1